2021
DOI: 10.3389/fcell.2021.784999
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Targets TRA-1/GLI Upstream of DAF-16/FOXO to Promote C. elegans Longevity and Healthspan

Abstract: Broccoli-derived isothiocyanate sulforaphane inhibits inflammation and cancer. Sulforaphane may support healthy aging, but the underlying detailed mechanisms are unclear. We used the C. elegans nematode model to address this question. Wild-type and 4 mutant C. elegans worm strains were fed in the presence or absence of sulforaphane and E. coli food bacteria transfected with RNA interference gene constructs. Kaplan–Meier survival analysis, live imaging of mobility and pharyngeal pumping, fluorescence microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…As such, functional changes associated with shifts in gene expression need to consider temporal and location information about the tissue in which these changes occur, to understand how information flows or is modulated, and what it means in a specific context. Indeed, HHLS is active throughout the development of the worm ( Hao et al, 2006c ; Kolotuev et al, 2009 ; Kouns et al, 2011 ; Oikonomou et al, 2011 ; Riveiro et al, 2017 ; Kume et al, 2019 ; Hong et al, 2021 ) and into aging ( Templeman et al, 2020 ; Ji et al, 2021 ), it concerns a variety of HRPs and PTRs with specific tissue-expression patterns ( Supplementary Figure 3 ) and non-redundant roles ( Zugasti et al, 2005 ; Hao et al, 2006b ; Baker et al, 2021 ). Tissue-specific omics datasets would thus greatly help disentangle the contributions of major tissues expressing HRPs and PTRs such as the nervous system, the hypodermis, the intestine, and the gonads, and of HHLS genes found co-expressed in several of them ( Supplementary Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, functional changes associated with shifts in gene expression need to consider temporal and location information about the tissue in which these changes occur, to understand how information flows or is modulated, and what it means in a specific context. Indeed, HHLS is active throughout the development of the worm ( Hao et al, 2006c ; Kolotuev et al, 2009 ; Kouns et al, 2011 ; Oikonomou et al, 2011 ; Riveiro et al, 2017 ; Kume et al, 2019 ; Hong et al, 2021 ) and into aging ( Templeman et al, 2020 ; Ji et al, 2021 ), it concerns a variety of HRPs and PTRs with specific tissue-expression patterns ( Supplementary Figure 3 ) and non-redundant roles ( Zugasti et al, 2005 ; Hao et al, 2006b ; Baker et al, 2021 ). Tissue-specific omics datasets would thus greatly help disentangle the contributions of major tissues expressing HRPs and PTRs such as the nervous system, the hypodermis, the intestine, and the gonads, and of HHLS genes found co-expressed in several of them ( Supplementary Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as C. elegans investment in reproduction often competes with mounting effective immune responses ( TeKippe and Aballay, 2010 ; Yunger et al, 2017 ; Anderson and Pukkila-Worley, 2020 ), HHLS could indirectly impact host-microbe interactions through their role in nematode reproduction, beyond the known developmental role of TRA-1 in sex determination ( Hodgkin, 1987 ; Berkseth et al, 2013 ; Ji et al, 2021 ), as shown for wrt-10 , ptc-1 , ptr-2 ( Kuwabara et al, 2000 ; MacNeil et al, 2013 ; Templeman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, EFL-1, promotes negative regulation of MPK-1 [ 64 , 65 ]. Genes regulated by TRA-1, which regulates hermaphrodite lifespan and healthspan upstream of the classical lifespan regulating transcription factor DAF-16 [ 66 ], were enriched among the genes upregulated in day 3 animals. Together, this makes a strong argument that krill oil achieves neuroprotection by slowing down the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted in triplicate, with each experimental group consisting of over 20 nematodes. The expression and cellular localization of the GFP-tagged allele were examined through fluorescence microscopy [ 72 , 73 ]. Mean fluorescence intensities were quantified using ImageJ as CTCF and normalized to the vehicle group.…”
Section: Methodsmentioning
confidence: 99%